PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION DENGAN STRES KERJA SEBAGAI VARIABEL INTERVENING - Hady Suganda; Sutrisno; Noni Setyorini (Transpublika Publisher, 2023)
This study attempts to investigate and analyze how leadership style, pay, and workplace environment affect employees' intentions to leave their jobs, with work stress acting as an influencing factor. There are 186 respondents in the research sample, all of whom work at Sarong Goyor UMKM in Pemalang Regency. This study used probability sampling, which uses a straightforward random sample procedure. The study data is handled using SmartPLS 3.0 software, and data analysis is done using the PLS-SEM (Partial Least Square-Structural Equation Model) methodology. The findings reveal the following results: Leadership style does not significantly affect turnover intention in Sarong Goyor UMKM in Pemalang Regency, as indicated by a P-Value of (0.281). Compensation has a significant impact on turnover intention in Sarong Goyor UMKM in Pemalang Regency, with a P-Value of (0.000). The work environment does not significantly influence turnover intention among Sarung Goyor UMKM in Pemalang Regency, with a P-Value of (0.799). Work stress does not significantly affect turnover intention, as indicated by a P-Value of (0.343). Leadership style does influence turnover intention, which is mediated by work stress, with a P-Value of (0.046). Compensation also has an impact on turnover intention, mediated by work stress, with a P-Value of (0.006). The work environment influences turnover intention, and this effect is mediated by work stress, with a P-Value of (0.000).